Delinquency Among Children Working on the Street in Aydın - Erel, Özlem; Özkök, Mustafa Selim; Katkıcı, Ufuk (The Bulletin of Legal Medicine, 2002)
To define the social demographic characteristics of the children working on the streets, their conditions, and whether there is a connection between working on the streets and children delinquency have been the aim of this study. We surveyed 70 children working on the streets with their consent, talking to them individualy face to face. Cases were in the age group of 7-17. 46 cases ( % 65.8 ) were students, as well as working after school. Their success at school was about % 85.7 average and below average. Most of them worked as shoe shiners ( % 64.3 ). In most of the cases, they have migrated to Aydın, they were a part of a crowded main family living in 2 or 3 roomed houses. They had no time for themselves to socialize or to play. Physical child abuse was found as % 54.3. Smoking rate was % 30.0. Using alcohol and drugs in the past was not determined. Up to present date, 13 cases have left home ( %18.6 ), out of these cases 8 of them slept on the streets through the night. It is thought that this is a risk factor for street children. Cases showed a rate of % 22.9 committed offences. The rate of committed offences were determined less among the children going to school compared with children who never went to school or left school. Key words: A child working on the street, child delinquency.